(untitled) (Journal of Economic Research & Business Administration, 2015)
One of the ways of development of the national economy is to elect a president – economic integration. And there is no doubt the right choice this way. Today, the integration of a booming global trend. Countries integrate into the world economy, and in the regions formed dozens of economic unions and communities aimed at closer political influence. Now the economy of the Republic of Kazakhstan is a significant player in world trade. For the development of world trade, Kazakhstan intends to join the WTO and therefore a lot of work done. There are also many messages. But WTO accession Kazakhstani goods should be subject to international standards. This problem makes it difficult to position the competitiveness of domestic products in both domestic and foreign markets. For this reason, agricultural products should be placed in the mainstream of high-tech manufacturing.